Nilai Religius Pada Cerita Rakyat Buaya Mangap (The Values of Religious in The Folklore of Buaya Mangap) - Momon Andriwinata; Zainal Rafli; Novi Anoegrajekti (Indonesian Language Education and Literature, 2023)
This study aims to describe and explain the value of religious character education in the Buaya Mangap folklore in Serang District, Banten Province. This study uses a qualitative method with an ethnographic study approach. The data were obtained from a collection of folklore obtained from interviews with respondents and other sources from the people of Serang Regency. Data analysis uses descriptive, analysis, and interpretation aspects which are reviewed by triangulation in terms of sources, methods, and theories. The results of the research show that this folklore contains two elements, namely the relationship between God and humans and between humans and fellow humans. The character values that can be internalized in everyday life include: getting used to reading prayers before doing activities, helping each other, and creating harmonization between communities.Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan nilai pendidikan karakter religius dalam cerita rakyat Buaya Mangap di Kabupaten Serang Provinsi Banten.Â Penelitian ini menggunakan metode kualitatif dengan pendekatan studi etnografi. Data diperoleh dari kumpulan cerita rakyat yang didapatkan dari hasil wawancara kepada responden serta sumber lain dari masyarakat Kabupaten Serang. Analisis data menggunakan aspek deskriptif, analisis, dan penafsiran yang ditinjau secara triangulasi dari sisi sumber, metode, dan teori. Hasil dari penelitian menunjukkan bahwa cerita rakyat ini mengandung dua unsur, yakni hubungan antara Tuhan dan manusia dan antara manusia dengan sesama manusia. Adapun nilai karakter yang dapat diinternalisasikan dalam kehidupan sehari-hari, antara lain: membiasakan membaca doa sebelum beraktivitas, saling menolong, dan menciptakan harmonisasi antar-masyarakat.